A critical review of AI-enhanced communication strategies in Southeast Asian startup ecosystems - Sonni, Alem Febri (Frontiers in Human Dynamics, 2026)
This mini review examines the intersection of digital disinformation, artificial intelligence technologies, and cultural identity construction within Southeast Asian startup ecosystems. Through systematic analysis of 68 peer-reviewed studies published between 2019 and 2024, we synthesize the current understanding of how AI-enhanced communication strategies both combat and potentially amplify disinformation while navigating complex cultural identity negotiations. Research demonstrates that culturally sensitive AI implementation increases funding success rates by 34% and market reach by 58% among religious minority entrepreneurs when appropriate algorithms are employed. The review identifies three critical research areas: algorithmic bias in cultural content moderation, the role of religious identity in digital entrepreneurship, and platform-specific adaptations of traditional communication frameworks. Our analysis reveals significant gaps in cross-cultural AI ethics research and proposes the “Cultural-AI Communication Convergence” (CAICF) framework, integrating Islamic communication principles with contemporary digital marketing practices. Findings suggest that while AI technologies offer promising solutions for combating disinformation, implementation must account for diverse cultural values and religious sensitivities to avoid marginalizing minority voices in digital spaces.